MH84 improves mitochondrial dysfunction in a mouse model of early Alzheimers disease - Pohland, Maximilian; Pellowska, Maren; Asseburg, Heike; Hagl, Stephanie; Reutzel, Martina; Joppe, Aljoscha; Berressem, Dirk; Eckert, Schamim H.; Wurglics, Mario; Schubert-Zsilavecz, Manfred; Eckert, Gunter P.; Justus Liebig University Giessen (My University, 2018)
Background: Current approved drugs for Alzheimers disease (AD) only attenuate symptoms, but do not cure the disease. The pirinixic acid derivate MH84 has been characterized as a dual gamma-secretase/proliferator activated receptor gamma (PPARgamma) modulator in vitro. Pharmacokinetic studies in mice showed that MH84 is bioavailable after oral administration and reaches the brain. We recently demonstrated that MH84 improved mitochondrial dysfunction in a cellular model of AD. In the present study, we extended the pharmacological characterization of MH84 to 3-month-old Thy-1 A beta PPSL mice (harboring the Swedish and London mutation in human amyloid precursor protein (APP)) which are characterized by enhanced AÎ²PP processing and cerebral mitochondrial dysfunction, representing a mouse model of early AD. Methods: Three-month-old Thy-1 A beta PPSL mice received 12 mg/kg b.w. MH84 by oral gavage once a day for 21 days. Mitochondrial respiration was analyzed in isolated brain mitochondria, and mitochondrial membrane potential and ATP levels were determined in dissociated brain cells. Citrate synthase (CS) activity was determined in brain tissues and MitoTracker Green fluorescence was measured in HEK293-A beta PPwt and HEK293-A beta PPsw cells. Soluble A beta 1-40 and A beta 1-42 levels were determined using ELISA. Western blot analysis and qRT-PCR were used to measure protein and mRNA levels, respectively.Results: MH84 reduced cerebral levels of the beta-secretase-related C99 peptide and of A beta 40 levels. Mitochondrial dysfunction was ameliorated by restoring complex IV (cytochrome-c oxidase) respiration, mitochondrial membrane potential, and levels of ATP. Induction of PPARÎ³ coactivator-1Î± (PGC-1Î±) mRNA and protein expression was identified as a possible mode of action that leads to increased mitochondrial mass as indicated by enhanced CS activity, OXPHOS levels, and MitoTracker Green fluorescence.Conclusions: MH84 modulates beta-secretase processing of APP and improves mitochondrial dysfunction by a PGC-1alpha-dependent mechanism. Thus, MH84 seems to be a new promising therapeutic agent with approved in-vivo activity for the treatment of AD.
Keywords: Alzheimers disease; Mitochondrial dysfunction; PPAR gamma activator; PGC-1 alpha; APP processing; ddc:610